Optimum component reallocation and system replacement maintenance for a used system with increasing minimal repair cost. (December 2020) - Fu, Yuqiang; Zhu, Xiaoyan; Ma, Xiaoyang
Highlights: Study the component reallocation based maintenance policy for the used system. A mixed binary nonlinear optimization model is established. Increasing minimal repair cost at failure. Analyze the relationship of the maintenance cost and the used age of system. Numerical examples show the efficiency of component reallocation. Abstract: Motivated by the economics of a used system, the paper studies a component reallocation (CR) based maintenance policy for a used and repairable system with functionally interchangeable components. The policy, denoted as optimum CR and system replacement maintenance, incorporates the actions of CR and system replacement to minimize the expected maintenance cost per unit time. The components experience nonhomogeneous degradation with different failure rates and different minimal repair costs because of different position conditions. The minimal repair costs are increasing over time. The CR action reallocates the functionally interchangeable components to balance degradation. The system replacement action replaces system by a new or used one. A mixed binary nonlinear optimization model for the policy is established to determine the optimal time and assignment for CR and the optimal time for system replacement. Further, we analyze the expected maintenance cost per unit time over the used age of system and some special cases. Finally, specializing the failure rate by Weibull distribution and the minimal repair cost by inversely proportional to the component reliability, numerical examples show the efficiency of CR compared to the system replacement maintenance without CR.